Ascending colon injury and ileal perforation due to blunt abdominal trauma: A case report - Toshiyuki Suzuki; Daisuke Sugiki; Akiyo Matsumoto; Takahiko Akao; Hiroshi Matsumoto (Radiology Case Reports, 2024)
A rare case of an ascending colon injury and ileal perforation in a 34-year-old male patient due to blunt abdominal trauma caused by a road traffic accident is reported in this study. This paper reports the clinical and imaging findings of seat belt syndrome. The seat belt syndrome primarily involves soft tissue injury; however, lacerations of the colon, small intestine, and mesentery have rarely been reported in the literature. However intestinal injuries, including bowel perforation and mesenteric injuries due to seat belt syndrome, must not be underestimated because they usually require emergency laparotomy because of accompanying peritonitis and hemorrhaging, and can be lethal if left untreated. Therefore, when an ascending mesocolon hematoma and free gas in the peritoneal cavity are present, gastrointestinal perforation due to seat belt syndrome should be suspected. In this case, gastrointestinal perforation was suspected based on the computed tomography findings, and emergency surgery was performed; the patient's course was uneventful without any postoperative complications. Early diagnosis and management are essential to prevent associated morbidity and mortality.